Catheterization related urethral injury in periphery due to improper technique - Pandit, Rakesh Kumar; Chaudhary, Sanjay; Jha, Vinay Kumar; Sah, Nilam; Thakur, Pawan Kumar (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Catheterization related urethral injury (CRUI), particularly in men, is common and produces significant morbidity. However, it seems to have gathered little interest of concerned authorities towards prevention. The objective of the study is to reveal that many CRUI are usually due to improper technique. Material and Methods: This is a retrospective and descriptive study carried out at Janaki Medical College & Teaching Hospital, Janakpur between May 2013 and September 2016. It included 18 male patients presenting in emergency with acute CRUI. Re-catheterization was attempted by experienced surgeons in them unless there was history suggestive of urethral stricture and the outcome was analyzed. Results: Mean age of the patients was 62.9 ± 17.7 (range: 22 - 90) years. When the consultant attended them, 8 (44.4%) patients had catheter in place with intraurethral balloon inflation (IUBI), and 10 patients had catheter removed. One patient in each group had scrotal hematoma suggesting urethral perforation. Excluding two patients with typical history suggestive of urethral stricture, manual urethral re-catheterization was attempted by surgeon in 16 patients and succeeded in 12 (75%) patients, which was remarkable. Rest of the 6 patients had suprapubic catheterization. Conclusion: Most of the CRUI results from technical fault and are potentially preventable. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4(1): 53-58